Expanding the phenotype of CACNA1C mutation disorders. Issue 6 (1st April 2021) - Gakenheimer‐Smith, Lindsey; Meyers, Lindsay; Lundahl, Derek; Menon, Shaji C.; Bunch, T. Jared; Sawyer, Briana L.; Tristani‐Firouzi, Martin; Etheridge, Susan P.
Abstract: Background: Pathogenic variants in the L‐type Ca 2+ channel gene CACNA1C cause a multi‐system disorder that includes severe long QT syndrome (LQTS), congenital heart disease, dysmorphic facial features, syndactyly, abnormal immune function, and neuropsychiatric disorders, collectively known as Timothy syndrome. In 2015, a variant in CACNA1C (p.R518C) was reported to cause cardiac‐only Timothy syndrome, a genetic disorder with a mixed phenotype of congenital heart disease, hypertrophic cardiomyopathy (HCM), and LQTS that lacked extra‐cardiac features. We have identified a family harboring the p.R518C pathogenic variant with a wider spectrum of clinical manifestations. Methods: A four‐generation family harboring the p.R518C pathogenic variant was reviewed in detail. The proband and his paternal great‐uncle underwent comprehensive cardiac gene panel testing, and his remaining family members underwent cascade testing for the p.R518C pathogenic variant. Results: In addition to displaying cardinal features of CACNA1C disorders including LQTS, congenital heart disease, HCM, and sudden cardiac death, family members manifested atrial fibrillation and sick sinus syndrome. Conclusion: Our report expands the cardiac phenotype of CACNA1C variants and reflects the variable expressivity of mutations in the L‐type Ca 2+ channel. Abstract : We present a four‐generation family harboring the CACNA1C p.R518C pathogenic variant that, in addition to displaying cardinal features of CACNA1C disorders including Long QT syndrome, congenital heart disease, hypertrophic cardiomyopathy, and sudden cardiac death, also manifest atrial fibrillation and sick sinus syndrome. Our report expands the cardiac phenotype of CACNA1C variants and reflects the variable expressivity of mutations in the L‐type calcium channel.